The Role of The Media in Revealing Social Problems - Murder Crime as An Example: An Analytical Study (Raparin Journal of Humanities (RJH), 2023)
Basically, There Are Two Types Of Murder, Deliberate Murder And Accidental Murder (Act Of God). This Study Is Devoted To Deliberate Murder, Such As (Murder For Money, Honor Killing Based On Honor Pretext, Murder By Torture, Murder As A Result Of Sexual Assault, Murder Of Children, Murder Due To Violence And Beating. However, As It Has Been Showcased in This Study, In Kurdistan Region Unlike Any Other Place, There Are Many Other Types of Murders on Various Reasons Such as Car Light Signaling, Pigeons, Children's Fights, Household Water Wells, Car Parking, Dog Fights, Roosters’ Fights, Gender Transition, Electricity Circuits, Chocolate, Land Properties, Religious Conversion, Leading in Folk Dance).   According To the World's Renowned Website (Our World in Data), In 2019 Alone, More Than (415,000) Thousand People Died in Deliberate Murder, Which Is Almost Three Times Higher Than the Number of Those Who Were Killed In Armed Clashes, Wars Terrorism And Conflicts On Countries’ Level. In Kurdistan Region, Although The Number Of Deliberate Killings Has Decreased In The Past Five Years, Yet Compared To Most Countries In The World, The Rate Is Still Alarming. In The Study’s Findings It Is Highlighted That Non-Compliance Of Media To Applicable Laws And Regulations, Lack Of Monitoring Of The Media In General In Presenting News On Murder, Showing Crime Related Programs And Movies And Lack Of Family Vigilance On The Use Of Electronic Games And Social Networks As Well As Lack Of Professional Journalists And Capable Staff, The Social Problem Of Murder Is More Evident And Has Affected The Mental State And Social Security Of Individuals And Families In Society.